Genetic evidence reveals improvement opportunities for tissue preparation in forensic analysis (2016)
Introduction: Paraffin embedded tissues are an excellent alternative to obtain dna, especially when it is not possible to have fresh samples or when the tissue storage and preservation is not feasible; therefore, this sample is the only item available for matching purposes. The success in any genetic analysis implies having adequate tissue fixation and suitable dna extraction methods that allow to obtain good quality and quantity molecules, free of biological, chemical and microbiological contaminants that can act as inhibitors in pcr amplification processes. Methods and Materials: In the genetics laboratory at the National Institute of Legal Medicine and Forensic Sciences, South-West Regional Office in Colombia, a preliminary test for validation of the dna extraction in paraffin embedded tissue was performed, using the validated organic method used as routine by the genetics laboratory in Bogotá, Colombia. Results and discussion: The effectiveness of the method based on the analysis of reproducibility, respectability and conformance was confirmed in terms of dna concentration, and acquisition of genetic profiles from dna extracts from four replicates of three different types of tissues obtained from a fetus, with respect to a blood sample in fta support. Conclusions: With the preliminary results obtained, some improvement opportunities were found for laboratories involved in the process.